BUILDING A COMPOSITE TEST TO MEASURE MOTOR AND SKILL COORDINATION FOR FEMALE SOCCER PLAYERS UNDER 17 YEARS OF AGE - Saher Mohammed Hameed (Proximus Journal Publishing, 2026)
This research aims to build a composite field test to measure motor coordination in female soccer players under 17 years of age, due to the essential role of coordination in developing skill performance, especially dribbling, passing, ball control, and shooting skills. The research adopted the descriptive approach using the field study method. The research population consisted of female players registered in premier league clubs for the 2024–2025 sports season. A composite test was designed that includes a skill sequence consisting of dribbling in a narrow corridor, passing to a teammate, controlling the ball, and then shooting at a divided goal. The validity of the test was verified through expert evaluation, and reliability was measured using the test–retest method on a pilot sample. The results showed that the test has a high degree of validity and reliability, and that motor coordination is positively associated with technical performance among female players. The research recommends adopting the test in women’s training programs and in selection and technical evaluation processes for youth female players
Keywords: motor coordination; youth female players; women’s socce; field tests